1997
DOI: 10.1212/wnl.48.4.1025
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and quality of life effects of differing dosages of tiagabine in epilepsy

Abstract: Tiagabine blocks the uptake by neurons or glia of synaptically released GABA resulting in prolonged GABAergic activity and decreased likelihood of epileptic seizures. We evaluated the cognitive and quality of life effects of tiagabine in a double-blind, add-on, placebo-controlled, parallel, multicenter, dose-response efficacy study in patients with focal epilepsy whose complex partial seizures were difficult to control. One hundred sixty-two patients provided cognitive and quality of life data for the analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(48 citation statements)
references
References 1 publication
3
44
0
1
Order By: Relevance
“…Nervousness describes the clinical side effects of tiagabine (Dodrill et al, 1997(Dodrill et al, , 1998(Dodrill et al, , 2000Adkins and Noble, 1998). In the absence of an accepted test for nervousness in rodents, we assumed that it can be assessed as a mild form of anxiety.…”
Section: Nervousness Versus Anxietymentioning
confidence: 99%
“…Nervousness describes the clinical side effects of tiagabine (Dodrill et al, 1997(Dodrill et al, , 1998(Dodrill et al, , 2000Adkins and Noble, 1998). In the absence of an accepted test for nervousness in rodents, we assumed that it can be assessed as a mild form of anxiety.…”
Section: Nervousness Versus Anxietymentioning
confidence: 99%
“…When present, the changes were small, and none reached statistically significant differences at the p < 0.01 level. Even if a slight negative impact of TGB with higher doses (56 mg/day) could not be completely discounted, it was considered not likely to be of clinical importance (29). Long-term TGB treatment did not cause cognitive impairment.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%
“…Additional adverse events identified in these and other open trials included tremor, nonconvulsive status epilepticus (absence stupor), emotional lability, vomiting, tiredness, headache, and psychosis. One study with class II evidence 29 showed with neuropsychometric tests that add-on tiagabine regimens were not associated with changes in cognitive functions.…”
mentioning
confidence: 99%